Tingkah Laku Awal Berahi Kambing Kaligesing (Capra aegagrus Hircus) Betina Yang Di Injeksi Ekstrak Hipofisa Dengan Level Berbeda - Delta Setiawan; Faruq Iskandar; Hanung Dhidik Arifin (Jurnal Riset Agribisnis dan Peternakan, 2019)
This study aims to determine the potential of goat pituitary extract on the heat cycle of the Kaligesing Goat. Improve the performance of the initial lustful behavior of the female Kaligesing Goat. The study was conducted in August 2018 until February 2019 at the Integrated Animal Husbandry Laboratory of the University of Muhammadiyah Purworejo. The material used was a pituitary extract of adult female goats and 24 female Kaligesing goats, aged 2-4 years. Medroxy progestagen acetate for sensual synchronization. The treatments used in the study were T0 (control) injection of 5 ml physiological NaCl 0.9%; T1 injection of pituitary extract 0.25 gr in 5 ml physiological NaCl 0.9%; T2 injection of 0.50 gr pituitary extract in 5 ml physiological NaCl 0.9%. The experimental design used in this study was a Completely Randomized Design (CRD) with 3 treatments and 8 replications. The parameters observed were riding other livestock, the sound frequency, and the behavior of moving the tail. The data obtained were analyzed descriptively and tested using Chi-square. The results showed that the administration of pituitary extract had no effect (P> 0.05) on all parameters. It was concluded that the administration of pituitary extract was able to show symptoms of heat but was not yet able to improve the performance of heat behavior.